Persistence of Interindustry Wage Differentials: A Reexamination Using Matched Worker‐Firm Panel Data - Goux, Dominique; Maurin, Eric (Journal of Labor Economics, 1999)
We estimate interindustry wage differentials using new French longitudinal data that allow a tracking of workers and their firms over time. We find that, when measured on a cross‐sectional basis, they primarily reflect the interindustry variations in unmeasured labor quality. However, interindustry wage differentials are only a minor component of interfirm wage differentials. The average differential in wages paid to the same workers by different firms is about 20%–30%. In a given industry, wage policies are more favorable to workers in large, capital‐intensive firms.